Peran Akuntansi Syariah dalam Pencegahan Fraud Pengelolaan Dana Haji - Eko Sudarmanto; Dwi Saleha; Irwan Irawadi Barus; Ahmad Zaki Mubarok; Mutia Pamikatsih (ITB AAS INDONESIA Surakarta, 2026)
The management of Hajj funds constitutes a public trust involving a substantial amount of pilgrims’ funds and a long-term management horizon. The complexity of fund management, exposure to moral hazard, and high public expectations make Hajj funds vulnerable to fraud if not supported by governance with strong integrity and an adequate accounting system. This study aims to examine the role of Islamic accounting in embedding the values of integrity and amanah (trustworthiness) as mechanisms for fraud prevention in the management of Hajj funds. The research employs a qualitative descriptive approach through a literature review of regulations governing Hajj fund management, particularly Law Number 34 of 2014, policies of the Hajj Financial Management Agency (BPKH), and Islamic accounting standards (Sharia Accounting Standards/PSAK Syariah). The findings indicate that Islamic accounting functions not only as a financial reporting system but also as an ethical instrument, an internal control mechanism, and a form of moral accountability grounded in Sharia values. The synergy between BPKH regulations and the implementation of PSAK Syariah plays a strategic role in narrowing opportunities for fraud and enhancing the trust of Hajj pilgrims as the rightful owners of the funds.